2017
DOI: 10.1051/matecconf/20179510009
|View full text |Cite
|
Sign up to set email alerts
|

Applying Triz for Production Quality Improvement

Abstract: Abstract. This paper aims to provide a thorough analysis on the application of TRIZ in improving the quality of canned food production. TRIZ tools such as engineering systems analysis, function analysis, cause and effect chain analysis, By-separation model and 40 Inventive Principles are applied in order to discover some feasible and elegant solutions to alleviate the problem. Findings revealed that the rejected canned products on the conveyor belt will be isolated or picked up with other good condition canned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…For example, Rupani et al [74] applied TRIZ to service improvement; Lee, Chen, and Trappey [75] focused on enhancing customer satisfaction; Maia et al [76] applied TRIZ to lean production. Swee [77] uses the TRIZ toolset to improve quality in the food industry. In addition, TRIZ can be used with other methods, such as Brad and Brad [78] combining TRIZ with SWOT analysis; Karnjanasomwong and Thawesaengskulthai [79] combining TRIZ with Pugh matrix; Lee, Leu, and Huang [80] by using FMEA, lean production, TRIZ, and 6 sigma to improve services.…”
Section: Research Hypothesis Modeling By Triz Methodsmentioning
confidence: 99%
“…For example, Rupani et al [74] applied TRIZ to service improvement; Lee, Chen, and Trappey [75] focused on enhancing customer satisfaction; Maia et al [76] applied TRIZ to lean production. Swee [77] uses the TRIZ toolset to improve quality in the food industry. In addition, TRIZ can be used with other methods, such as Brad and Brad [78] combining TRIZ with SWOT analysis; Karnjanasomwong and Thawesaengskulthai [79] combining TRIZ with Pugh matrix; Lee, Leu, and Huang [80] by using FMEA, lean production, TRIZ, and 6 sigma to improve services.…”
Section: Research Hypothesis Modeling By Triz Methodsmentioning
confidence: 99%
“…Through extensive analysis of tens of thousands of patents, Altshuller observed that technology adheres to a set of rules. These rules can be studied and utilized e-ISSN: 2682-8383 8 to enhance existing systems and discover innovative problem-solving approaches [12]. Altshuller formulated a framework for engineering evolution tendencies and emphasized the significance of identifying and resolving conflicts in overcoming challenging innovation problems.…”
Section: B Theory Of Inventive Problem Solving (Triz)mentioning
confidence: 99%
“…CEC analysis helps to identify the correct cause(s) of the problem. If the wrong cause is identified, it will lead to an unsuccessful response [21]. In essence, CEC analysis is similar to the "5 Whys" process of continuously eliciting the causes of the problem by asking "why", moving from high-level causes to low-level causes [22].…”
Section: Principles Of Triz Appliedmentioning
confidence: 99%